Evaluating the Effectiveness of Village Fund Allocation in Supporting Participatory Rural Development and Reducing Poverty Rates in Remote Areas of East Nusa Tenggara - Ama, Maria Yosepha Dapa; Nugroho, Arif Prasetyo (Moccasin Journal De Public Perspective, 2025)
The Village Fund program in Indonesia is a flagship policy designed to strengthen decentralization, promote participative rural development, and reduce poverty. This study evaluates its effectiveness in remote areas of East Nusa Tenggara (NTT), a province marked by poverty, isolation, and socio-economic vulnerability. Using a qualitative case study, data were gathered through interviews, focus-group discussions, and field observations in Manggarai Timur, Sumba Timur, and Alor. Findings show that the Village Fund significantly improved infrastructure such as roads, irrigation, and clean water systems, enhancing connectivity and reducing isolation. Participatory processes like village meetings (musyawarah desa) opened new channels for community involvement, though their quality varied across regions. Yet, the impact on poverty reduction remains limited due to weak institutional capacity, elite dominance, and the absence of livelihood-based projects. The study concludes that infrastructure investment alone cannot address multidimensional poverty without integrating education, health, and climate resilience. Strengthening community participation, transparency, and local government capacity are crucial for maximizing program effectiveness and ensuring inclusive, context-sensitive rural development.